Peran Guru Pendidikan Agama Islam dalam Membentuk Resiliensi Siswa di SMA Negeri 1 Dayeuhluhur Kabupaten Cilacap - Rachmawati, Defi; Wanojaleni, Kartika (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2022)
The purpose of this study was to find out the role of Islamic Religious Education teachers in building student resilience at SMA Negeri 1 Dayeuhluhur, Cilacap Regency. The findings in this study are that the problems experienced by students are parental divorce, economic difficulties, and broken homes, student resilience is at a normal or average level. the biggest factors forming student resilience are parents or family, personal self, and peers, Islamic Religious Education teachers have a role in shaping the resilience of students of SMA Negeri 1 Dayeuhluhur (1) as mentors, through the application of spiritual values in habituation activities dhuha prayer, tadarus, literacy, weekly infaq which is implemented at Dayeuhluhur 1 Public High School. (2)as a role model and (3) as a motivator, which is carried out by Islamic Religious Education teachers when learning is in progress, while Islamic Religious Education materials that encourage the formation of student resilience include self-control (Mujahadah Al Nafsi), faith in Allah SWT., and ethics in Muslim/Muslim clothing.